Pengaruh Metode Drill terhadap Keterampilan Bermain Bolavoli Mini pada Siswa Sekolah Dasar - astuti, yuni (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
Sports activities on the younger generation has the objective to finalize the change or human resources. This sport consists of sports education, sports recreation, sports achievement, amateur sports, professional sports and sports persons with disabilities. In this case the author discusses sports education means the physical education and sport carried out as part of the educational process of regular and continuing to acquire knowledge, personality, ability, health and physical fitness of the students who take part in the sport. Drill method is better. The method was applied to students of State Elementary School 14 Jambak District of Koto Kampung Padang Kota Tangah and more effective than the method of playing the mini volleyball playing skills.